Evaluating green and sustainable chemistry education through students’ interventions - Daniel Nikolovski; Marina Stojanovska (Macedonian Journal of Chemistry and Chemical Engineering)
This study explores the integration of green and sustainable chemistry into educational curricula and its impact on students' knowledge, motivation, and perceptions. The research aimed to evaluate whether activities centered on green and sustainable chemistry improve students' academic performance and foster awareness of sustainability concepts. Conducted between April and June 2024 in three primary schools in Macedonia, the study involved 211 8th grade students, divided into a control group and an experimental group. While the control group followed standard lessons, the experimental group participated in specific activities integrated into the topic "Introduction to Organic Chemistry." A mixed-methods approach was employed, combining quantitative tools such as the conceptual knowledge test and the activity perception questionnaire, alongside qualitative methods like focus groups and semi-structured interviews. The conceptual knowledge test assessed students' academic achievements, while the activity perception questionnaire evaluated their perceptions of the activities. The results showed no significant difference in academic performance between the two groups. However, the activity perception questionnaire revealed that students in the experimental group found the activities engaging, valuable, and effective in enhancing their understanding of green and sustainable chemistry concepts. Qualitative data further indicated a preference for interactive learning methods like research, games, and experiments, which fostered greater motivation and collaboration among students. This study underscores the importance of integrating green and sustainable chemistry into curricula to promote environmental awareness and sustainable practices. These findings provide insights into effective teaching strategies and support the inclusion of green and sustainable chemistry in educational policies to equip students for global environmental challenges.